Design of a high-resolution Rayleigh-Taylor experiment with the Crystal Backlighter Imager on the National Ignition Facility. (1st February 2022) - Angulo, A.M.; Nagel, S.R.; Huntington, C.M.; Weber, C.; Robey, H.F.; Hall, G.N.; Pickworth, L.; Kuranz, C.C.
Abstract: The Rayleigh-Taylor (RT) instability affects a vast range of High Energy Density (HED) length scales, spanning from supernova explosions (10 13 m) to inertial confinement fusion (10 -6 m). In inertial confinement fusion, the RT instability is known to induce mixing or turbulent transition, which in turn cools the hot spot and hinders ignition. The fine-scale features of the RT instability, which are difficult to image in HED physics, may help determine if the system is mixing or is transitioning to turbulence. Earlier diagnostics lacked the spatial and temporal resolution necessary to diagnose the dynamics that occur along the RT structure. A recently developed diagnostic, the Crystal Backlighter Imager (CBI), [1, 2] can now produce an x-ray radiograph capable of resolving the fine-scale features expected in these RT unstable systems. This paper describes an experimental design that adapts a well-characterized National Ignition Facility (NIF) platform to accommodate the CBI diagnostic. Simulations and synthetic radiographs highlight the resolution capabilities of the CBI in comparison to previous diagnostics. The improved resolution of the system can provide new observations to study the RT instability's involvement in mixing and the transition to turbulence in the HED regime.